PENGANGKUTAN ONLINE DITINJAU DARI UNDANG-UNDANG NOMOR 22 TAHUN 2009 (Faculty of Law, University of Dr. Soetomo, 2019)
Online transportation is a transportation service that utilizes technological advancements, whose aim is to facilitate all human activities that are carried out daily. The problem that will be discussed in this research is the arrangement of online transportation in terms of Law No. 22 of 2009 concerning Road Traffic and Transportation. This normative law research uses a conceptual approach and a statue approach with qualitative descriptive analysis. Research Results, Law No. 22 of 2009 concerning LLAJ has not yet regulated online-based transportation, however, the safety, security and comfort requirements in UULLAJ are still being observed and the government has issued regulations that can become legal umbrella for the implementation of online-based transportation, namely: Government Regulation No. 74 of 2014 concerning Road Transportation; Minister of Transportation Regulation No. 32 of 2016 concerning the Implementation of Transportation of People with Public Motor Vehicles Not in Route revised to Permenhub No. 108 of 2017; Permenhub No. 118 of 2018 concerning the Implementation of Rental Vehicles; Permenhub No. 12 of 2019 concerning Safety Protection of Motorcycle Users Used for the Interest of the Community.Keywords : Arrangement, Transportation, Online, Law